Contribution of homeownership towards liveable city: a case study of Kuala Lumpur - Jong, Suk Lee (2025)
Homeownership plays a crucial role in shaping the foundations of urban livability, serving as a cornerstone in creating a vibrant and sustainable city. In the context of Kuala Lumpur, the attainment of homeownership is influenced by a variety of factors, including financial considerations, geographical location, government policies, developer strategies, and lifestyle preferences. These factors collectively form a complex landscape that shapes the ability of individuals, particularly within middle- and low-income groups, to achieve homeownership. Income levels, accessibility, and housing affordability are critical components in this dynamic, underscoring the importance of a multi-faceted approach to understanding how homeownership contributes to the broader concept of a livable city. Given the significance of these influences, this study seeks to explore how these elements interact to promote or hinder homeownership in Kuala Lumpur.